An analytical numerical procedure for the measurement of pollution in a system of interconnecting lakes - Ghosh, Indranil; Chowdhury, Md. Sazzad Hossien; Mt Aznam, Suazlan (2020)
Pollution has become a very serious threat to our environment. Using deferential equations, monitoring pollution has become a useful tool in saving the air, water, and soil to pave the way of Sustainable Development Goals (SDGs). Although just a monitoring device, deferential equations, used by people that care about what is happening to the environment, can be a solution to the problems. Showing the simplicity of the lake pollution model and it's three cases of input functions, just we used numerical technique the New Iterative Method (NIM) on this model with decent accuracy. Comparisons with the standard fourth order Runge Kutta method (RK4) results and the results obtained by the New Iterative Method (NIM) shows that NIM is a powerful efficient procedure for measurement of pollutant in systems of interconnecting lakes.